2013
DOI: 10.3899/jrheum.120879
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers in Relapsing Antineutrophil Cytoplasmic Antibody-associated Vasculitis

Abstract: Objective Glomerulonephritis (GN) is common in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), but tools for early detection of renal involvement are imperfect. We investigated 4 urinary proteins as markers of active renal AAV: alpha-1 acid glycoprotein (AGP), kidney injury molecule-1 (KIM-1), monocyte chemoattractant protein-1 (MCP-1), and neutrophil gelatinase-associated lipocalin (NGAL). Methods Patients with active renal AAV (n = 20), active nonrenal AAV (n = 16), and AAV in longt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 42 publications
1
27
0
6
Order By: Relevance
“…The C-X-C motif chemokine 13 (CXCL13) also known as B lymphocyte chemoattractant (BLC), the matrix metalloproteinase-3 (MMP-3), and TIMP metallopeptidase inhibitor 1 (TIMP-1) are the best-performing markers in discriminating active disease from remission, even if compared with reactive protein C (CPR) and erythrocyte sedimentation rate (ESR). [23] Additional potential biomarkers in patients with vasculitides are represented by monocyte chemoattractant protein-1 (MCP-1), [24] the von Willebrand factor antigen, [25] the Pentraxin-3 (PTX3), [26] and the Eotaxin-3. [27,28] A summary of the main studies focused on possible biomarkers in patients with vasculitides is reported in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…The C-X-C motif chemokine 13 (CXCL13) also known as B lymphocyte chemoattractant (BLC), the matrix metalloproteinase-3 (MMP-3), and TIMP metallopeptidase inhibitor 1 (TIMP-1) are the best-performing markers in discriminating active disease from remission, even if compared with reactive protein C (CPR) and erythrocyte sedimentation rate (ESR). [23] Additional potential biomarkers in patients with vasculitides are represented by monocyte chemoattractant protein-1 (MCP-1), [24] the von Willebrand factor antigen, [25] the Pentraxin-3 (PTX3), [26] and the Eotaxin-3. [27,28] A summary of the main studies focused on possible biomarkers in patients with vasculitides is reported in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of significant proteinuria is an important marker for staging and prognosis in Henoch-Schoenlein purpura and is often used to make decisions regarding treatment. However, once kidney damage has occurred due to GN, proteinuria, hematuria, and even red blood cell casts may persist without evidence of progressive kidney disease [4,5], so the high sensitivity and specificity of different aspects of urinalysis are apparent only during the first episode of GN. Discovery of urinary markers of active kidney damage would appear to be plausible [5-7], but such markers have not reached clinical use in vasculitis.…”
Section: Accepted Biomarkers In Vasculitismentioning
confidence: 99%
“…Связывание МСР-1 с CCR2 сопровождается как моноцитарной инфильтрацией, так и пролиферацией эпителиальных, эндотелиальных и сосудистых гладкомышечных клеток. Участие MCP-1 в воспалительном процессе в почечной паренхиме, а значит и в ремоделировании почечной ткани подтверждается тем, что уровень МСР-1 в моче повышается в период обострения гломерулонефрита как в первичном [5], так и вторичном его варианте, например, при системной красной волчанке [6] и системных васкулитах [7]. Важной морфологической особенностью является то, что при пролиферативных формах гломерулонефритов уровень МСР в моче был выше, чем при непролиферативных формах [8].…”
Section: Discussionunclassified